Comparative analysis of the productivity and power of the crushing process by compression and shear loading in jaw crushers with simple and parallel-circular jaw movement - Malich, M.G.; Katan, V.O.; Laikov, D.V.; Avramenko , S.O. (Theory and Practice of Metallurgy, 2024)
Objective. To carry out a comparative analysis of the productivity and efficiency of the crushing process by compression and shear load in jaw crushers with simple and parallel-circular motion. Methods. A comparative analysis of the kinematic features of the movable jaw drive mechanisms for crushers with simple movement of the trajectory of the working surface points, with complex movement of the traditional design, and with parallel-circular movement of the jaw along its entire length was used to analyze the productivity and power of the process. Results. The paper analyzes the operation of the most common traditional kinematic schemes of jaw crushers with simple movement and complex jaw movement. A jaw crusher with a circular motion of the movable jaw along its entire length is considered in detail, which provides an increase in its productivity by increasing the cycle time for unloading the crushed material by almost a quarter. The power to overcome friction forces during the destruction of rock pieces was calculated. Calculations for various types of rocks have shown that a jaw crusher with a circular movement of the movable jaw along its entire length, due to shear load, theoretically requires significantly less (on average, 2 times) power to crush rock at all the same chamber dimensions and crushing conditions than a traditional jaw crusher with a simple jaw movement. Scientific innovation. A jaw crusher with circular motion of the movable jaw along its entire length, with rational productivity, theoretically requires significantly less (on average 1.76 times) power for crushing rock, taking into account friction costs, with all the same chamber dimensions and crushing conditions, than a traditional jaw crusher with simple jaw motion. Practical significance. The presented kinematic scheme of a crusher with a parallel-circular movement of the jaw along its entire length theoretically requires significantly less power and therefore will have a higher level of energy efficiency, which directly affects the economic performance of the crushing process. Energy efficiency and increased productivity can become key market competitiveness criteria.